Análisis de cobertura de la señal wifi para la FAFI mediante un programa gráfico - Chacón Peralta, José Andrés (2021)
Wi-Fi connectivity is based on radio waves between the access points and the wireless device that has requested the downloading of files, emails, Internet browsing, among others. Due to the COVID 19 pandemic, the use of the internet has become a vitally important service for the development of academic activities in educational institutions, however, the quality of the service directly impacts its success or failure. At the Technical University of Babahoyo, large investments have always been made with respect to internet service, currently they have signed a contract with the company In.Planet SA, the Faculty of Administration, Finance and Information Technology receives approximately 300megas to the free PortiUTB network . For the present case study, an inventory of the connected network devices was carried out and the analysis of the signal strengths on each floor of the building, the Wifiman mobile app was used and it was possible to find different levels of Wi-Fi network coverage. After conducting the study, it is suggested to install more internet access points, especially on the upper floor to guarantee internet service for students and teachers.